The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1016/j.jalz.2009.04.690
|View full text |Cite
|
Sign up to set email alerts
|

P4‐224: Epigenetic control of Aquaporin 1 expression by the amyloid precursor protein

Abstract: Cellular processing of the amyloid precursor protein (APP) has been extensively studied, but its precise function remains elusive. The intracellular domain of APP has been proposed to regulate expression of several genes by mechanisms that are largely unknown. We report that APP regulates expression of the aquaporin 1 (AQP1) gene in mouse embryonic fibroblasts and in transgenic mice. AQP1 mRNA and protein were down-regulated in fibroblasts lacking APP or presenilin 2 in which AQP1 expression was restored by st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 33 publications
1
15
0
Order By: Relevance
“…Overexpression of AQP1 has been evidenced in autoimmune and alcoholic pancreatitis (42), in Alzheimer disease (43), as well as in rheumatoid and psoriatic arthritis cases (44). AQP4 expression is enhanced in the brain of Alzheimer disease patients and cerebral amyloid angiopathy patients (43,45).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Overexpression of AQP1 has been evidenced in autoimmune and alcoholic pancreatitis (42), in Alzheimer disease (43), as well as in rheumatoid and psoriatic arthritis cases (44). AQP4 expression is enhanced in the brain of Alzheimer disease patients and cerebral amyloid angiopathy patients (43,45).…”
Section: Discussionmentioning
confidence: 99%
“…Overexpression of AQP1 has been evidenced in autoimmune and alcoholic pancreatitis (42), in Alzheimer disease (43), as well as in rheumatoid and psoriatic arthritis cases (44). AQP4 expression is enhanced in the brain of Alzheimer disease patients and cerebral amyloid angiopathy patients (43,45). AQP5 polymorphisms have been associated with chronic obstructive pulmonary disease and chronic inflammation in smoking patients and survival rate in severe sepsis (46,47).…”
Section: Discussionmentioning
confidence: 99%
“…While, these studies are in direct contrast to our observation of hyperacetylation and downregulation of Bdnf expression, it is by no means a novel phenomenon. Huysseune et al (2009) recently showed that hyperacetylation induced by TSA treatment in mouse fibroblasts that express APP actually decreases the mRNA levels of aquaporin 1 and this downregulation is dependent on de novo protein synthesis, suggesting that a repressive element is upregulated after TSA treatment. Therefore, it is reasonable to deduce that the increased hyperacetylation we observe in cultured neurons in this study is either not substantially contributing to Bdnf promoter regulation or that some other repressive protein(s) upregulated by increased histone acetylation may be acting to diminish Bdnf mRNA levels.…”
Section: Discussionmentioning
confidence: 99%
“…This suggestion gave rise to conflicting results and interpretations, 9,10 but very recent work unraveled new genes regulated by AICD and showed that their regulation relies on an epigenetic mechanism. 30,31 Although this mechanism awaits further characterization, cleavage at ε site and AICD could play an essential role in APP function or during AD, independently of Aβ, by controlling gene expression. It is therefore of prime interest to understand if dimerization has similar regulatory roles in Aβ and AICD production.…”
Section: Therapeutical Outcomesmentioning
confidence: 99%